Balancing Work and Motherhood: Looking at the Experiences of Working Mothers in Aotearoa/New Zealand - Barclay, Shannon (Auckland University of Technology, 2021)
This study investigates how women in Aotearoa/New Zealand balance work and family. The objective of this study is to determine what could be changed or improved to support women as mothers and workers in Aotearoa/New Zealand. Drawing from one-on-one semi-structured interviews with six working mothers, five Pakeha and one Māori, I explore how Aotearoa/New Zealand mothers negotiated the demands of paid work and mothering. Also, I analyse how organisational and governmental policies and practices impacted their balance of work and family. When I embarked on this project, my initial focus was finding how women in leadership positions juggle motherhood and work. However, when I began the interview process with the women, I realised that leadership was not the focus of our discussions. The focus was more on how they strived to balance their work and family life, regardless of their leadership experiences. I studied the women’s talk through a feminist lens, and conducted a thematic narrative analysis (Riessman, 1993). I also used Giddens’ (1984) theory on structure and agency as a tool to investigate how social expectations, gendered power, and one’s subjective identity, work within women’s lives. My analysis of the women’s talk uncovered an overwhelming sense of guilt, especially when the women felt they were not giving enough energy to their work or children. Also, the women experienced a gap between their prenatal expectations that motherhood would come naturally, versus their postnatal lived experiences. These negative postnatal experiences surfaced when the women felt they were deviating from the “rules” of oppressive mothering structures (Giddens, 1984, p. 184). Also, the women commonly used flexible working arrangements to balance work and family, which had their advantages and disadvantages. I conclude that many of the issues the women faced were due to the highly gendered structure of society, which needs to change to stop unfairly guilting women so they can balance work and family life. I outline the changes and improvements that could occur in the household, workplace, or in government policy.
Keywords: Motherhood; Mothering; Family; Work; Working mother; Feminism; Feminist lens; Aotearoa; New Zealand; Giddens; Structure; Agency; Mothering expectations; Mothering guilt; Mother guilt; Flexible working; Gender; Work and family